Biologically Active Orbitides from the Euphorbiaceae Family - Ramalho, Suelem D. [UNESP]; Pinto, Meri Emili F. [UNESP]; Ferreira, Douglas; Bolzani, Vanderlan S. [UNESP] (Thieme, 2018)
A comprehensive overview of natural orbitides isolated from Euphorbiaceae species and their most relevant biological activities are presented. Euphorbiaceae is a large and diverse family, which comprises about 300 genera, and is known as an important source of medicines and toxins. Several classes of secondary metabolites have been described for this taxon, however, orbitides have been broadly reported in Jatropha and Croton genera. Additionally, the latex is documented as the main source of orbitides in this family. Based on their structural and functional diversity, orbitides present a large variety of biological activities described as cytotoxicity, antimalarial, antibacterial, antifungal, enzymatic inhibition, and immunosuppressive, although the mechanism of action still needs to be further investigated. In recent years, the discovery of bioactive cyclic peptides from different sources has grown exponentially, making them promising molecules in the search for new drug leads. This review also highlights the attempts made by many researchers to organize the orbitides nomenclature and amino acid numbering, as well the important progress recently achieved in the biosynthetic study area.
Keywords: Croton; cyclic peptides; Euphorbiaceae; Jatropha; orbitides